Variability in tongue pressure among elderly and young healthy cohorts: A systematic review and meta‐analysis. (15th September 2020) - Arakawa, Itsuka; Igarashi, Kensuke; Imamura, Yoshiki; Müller, Frauke; Abou‐Ayash, Samir; Schimmel, Martin
Abstract: Objectives: Tongue pressure (TP) is used for the diagnosis of oral hypofunction; however, the impact of several variables on TP is unclear. Therefore, the current systematic review and meta‐analysis aimed to analyse the variability in tongue pressure among healthy individuals aged ≥60 years vs <60 years. Secondary outcomes were the influence of gender and the type of measuring device (Iowa Oral Performance Instrument (IOPI) vs JMS tongue pressure measurement device (JMS)). Methods: PubMed and the Japanese database Ichushi‐Web were searched systematically by two independent reviewers for studies reporting TP values in healthy populations. Clinical studies published between 1959 and June 2020 with more than 10 participants, written in English, German or Japanese, were included. A random‐effects meta‐regression for aggregate‐level data was applied (α < 0.05). Results: Sixty‐eight studies reported TP for a total of 13 773 subjects aged <60 years (n = 3265) and ≥60 years (n = 10 508). TP was significantly higher in subjects <60 years (estimated weighted mean (EWM) ± standard error = 51.9 ± 1.28 kPa; 95% CI = 49.4‐54.4) relative to those ≥60 (EWM = 34.7 ± 0.94 kPa; 95% CI = 32.8‐36.5) ( P < .001), men (EWM = 45.9 ± 2.09 kPa; 95% CI = 41.8‐50.0) relative to women (EWM = 39.3 ± 1.68 kPa; 95% CI = 36.0‐42.6) ( P = .015) and when assessed with the IOPI (EWM = 51.9 ± 1.32 kPa; 95% CI = 49.3‐54.5) compared to the JMS (EWM = 33.5 ± 0.63 kPa; 95% CI = 32.2‐34.7) ( P < .001). In terms of gender, there was no significant difference in TP among subjects ≥60 years ( P = .282). However, in subjects younger than 60, a significant difference was observed ( P = .004). Conclusions: Healthy populations aged <60 years showed significantly higher TP than those aged ≥60 years. TP values ascertained by the IOPI are significantly higher than those obtained with the JMS.